Estimation of vitamin D level in low backache cases and their outcome after treatment with vitamin D - Khanna, Mohit; Dahiya, Amit; Garg, Abhishek; Yadav, Umesh; Sheoran, Ajay; Dutta, Mayank; Singh, Lovjot; Sharma, Rakesh; ., Amit (International Journal of Research in Orthopaedics, 2020)
Background: Vitamin D has a significant role to play in bone metabolism and neuromuscular function. Several researchers have indicated that vitamin D deficiency may be possibly related to chronic musculoskeletal pain including chronic low back pain (CLBP). Objectives of this present study were conducted to rule out the vitamin D deficiency in a patient can also be a cause of low backache other than various spinal disorders like PIVD, spondylolisthesis etc. Methods: A total of 50 patients, of any age who visited the Department of Orthopedics outpatient/Emergency, with chief complaint of low backache without any low backache disease like PIVD and spondylolisthesis etc. were thoroughly interviewed and examined for any concomitant pathological disease of spine. Patient’s Blood sample of about 5 ml with syringe of 10 cc. were taken and the serum vitamin D level was assayed by “direct competitive chemiluminescence immunoassay” (CLIA). Results: Out of 50 patients of low backache and vitamin D deficiency, 33 patients have good outcome in their pain after getting treatment in form of Vitamin D. Conclusions: We concluded that the vitamin D plays a major role in low backache and after treatment there is significant improvement in low backache.